Market power in the market for greenhouse gas emissions permits: The interplay with the fossil fuel markezs - Cathrine Hagem; Ottar Mæstad (University of Oslo, Department of Economics, 2002)
Implementation of the Kyoto Protocol is likely to leave Russia and other Eastern European countries with market power in the market for emission permits. Ceteris paribus, this will raise the permit price above the competitive permit price. However, Russia is also a large exporter of fossil fuels. A high price on emission permits may lower the producer price on fossil fuels. Thus, if Russia coordinates its permit market and fossil fuel market policies, market power will not necessarily lead to a higher permit price. Fossil fuel producers may also exert market power in the permit market, provided they conceive the permit price to be influenced by their production volumes. If higher volumes drive up the permit price, Russian fuel producers may become more aggressive relative to their competitors in the fuel markets if the sale of fuels is coordinated with the sale of permits. The result is reversed if high fuel production drives the permit price down.
Keywords: L13; Q28; Q48; 330; Climate policy; gas; market power; emission permits; Umweltpolitik; Klimaveränderung; Marktmacht; Emissionsrechte; Theorie; Osteuropa; Russland